PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN KOMPETENSI, TERHADAP KINERJA KARYAWAN PERUSAHAAN DAERAH PASAR PALEMBANG JAYA - Abdul Rizal; Fakhry Zamzam; Luis Marnisah (Program Magister Manajemen Indo Global Mandiri University, 2021)
The purpose of this study was to determine the results of the analysis of the influence of organizational culture, competence and compensation both partially and simulatively on the performance of Palembang Palembang Regional Market Company Palembang City. The study used a confirmatory survey method with a quantitative approach, a population of 220 employees of Palembang Jaya Regional Market Company Palembang City, 142 taken as a sample of research using a Sloven formula, data collection using questionnaire techniques, documentation and observation. Data processing uses the spss version 23 analysis tools. Research time is from November 2019 to January 2020. Results Data output is processed with SPSS, that organizational culture has a positive and significant effect on performance with a significance level of 0.00 <0.05 and t table 7.552> t count 2.003 regression coefficient of o, 538; that partially the competence has a positive and significant effect on performance with a significance level of 0.00 <0.05 and t table 5.949> t count 2.003 regression coefficient 0.450; that partially, compensation has a positive and significant effect on performance with a significance level of 0.00 <0.05 and t table 7.667> t count 2.003 regression coefficient of 0.545; and simultaneously organizational culture, competence and compensation affect the performance of t count 8.599> t table 4.763 regression coefficient of 47.1% the rest 52.9% influenced by other variables. Research conclusions that (1) employee organizational culture always work together in a work team, have a positive and significant effect on improving performance through leadership support in employee development, (2) employee competence by getting enough facilities to run, tasks have a positive and significant impact on performance through leadership support in employee development; (3) Compensation to employees in the form of adequate facilities in carrying out tasks, positively and significantly influencing performance through leadership support for employee development, (4) Organizational Culture, Competence and Compensation simultaneously affect the performance improvement of Palembang Palembang Pasar Daerah Regional Company with a regression reached 47.1%, while another 52.9% was influenced by variations of other variables. The most influential variable in improving performance at the Palembang Jaya Regional Market Company was to increase employee compensation by considering workload,